2013
DOI: 10.2147/ppa.s40577
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of asthmatic and nonasthmatic children to physical exercise

Abstract: PurposeThe aim of this study was to examine the physical activity of children with and without asthma in Greece, the factors affecting their intention to exercise, and the influence of gender.MethodThe study involved 50 children with asthma and 50 children without asthma, aged 9–14-years old. We used the leisure time exercise questionnaire to assess the frequency and intensity of exercise. The planned behavior scale examined seven factors affecting physical activity: attitude, intention, self-identity, attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…It has been noted that despite asthmatic children taking part in less physical activity or activity that is mild and moderate, there is no significant difference between the positive attitudes of asthmatic children and their non-asthmatic peers toward exercise 21…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that despite asthmatic children taking part in less physical activity or activity that is mild and moderate, there is no significant difference between the positive attitudes of asthmatic children and their non-asthmatic peers toward exercise 21…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies continue to show that asthmatic children practice less PA than their peers, 6 , 7 , 8 although it is not a consensus. 3 , 4 , 9 These data point to a possible behavioral differentiation between asthmatics and the general population regarding physical activity.…”
Section: Introductionmentioning
confidence: 76%
“…According to Battilani el al., 27 even with all the knowledge acquired on the practice of PA, asthmatic patients presented lower physical fitness compared to a non-asthmatic control group. In contrast, Dimitrakaki et al 3 and Eijkemans et al 28 reported that no difference in physical activity frequency was found among children with and without asthma. Wanrooij et al 4 concluded that the beneficial effects of physical exercise and the lack of negative effects indicate its recommendation in children with asthma.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations